Assessment of water quality index and heavy metal contamination in active and abandoned iron ore mining sites in Pahang, Malaysia - Madzin, Zafira; Mohd Kusin, Faradiella; Mohd Yusof, Fasihah; Muhammad, Siti Nurjaliah (EDP Sciences, 2016)
The composition of heavy metals in water and surface soils of iron ore mining sites were investigated to evaluate on the potential occurrence of heavy metal contamination. Physico-chemical characteristics of the waters were also investigated to determine the current status of water quality index (WQI) of the sites. Samples of water and surface soils of active mine (Kuala Lipis) and abandoned mine (Bukit Ibam) in Pahang were collected at four locations, respectively. The physico-chemical parameters measured for WQI were pH, dissolved oxygen, biological oxygen demand (BOD), chemical oxygen demand (COD), suspended solids (SS), and ammoniacal nitrogen (AN). The water quality parameters were classified according to the Department of Environment (DOE) water quality classification. The study revealed that most of the sites in Bukit Ibam and Kuala Lipis were categorized as clean to slightly polluted. On the other hand, heavy metal analysis in water showed that aluminium and manganese level in both sites have exceeded the allowable limits for raw and treated water standards by the Ministry of Health. For heavy metal compositions in soils showed most of the heavy metal concentrations were below the recommended guideline values except for lead, arsenic, zinc and copper.